Assessed and discharged - diagnosis, mortality and revisits in short-term emergency department contacts - Hassan Al-Mashat; Tim A. Lindskou; Jørn M. Møller; Marc Ludwig; Erika F. Christensen; Morten B. Søvsø (BMC, 2022)
Abstract Background Emergency departments (EDs) experience an increasing number of patients. High patient flow are incentives for short duration of ED stay which may pose a challenge for patient diagnostics and care implying risk of ED revisits or increased mortality. Four hours are often used as a target time to decide whether to admit or discharge a patient. Objective To investigate and compare the diagnostic pattern, risk of revisits and short-term mortality for ED patients with a length of stay of less than 4 h (visits) with 4-24 h stay (short stay visits). Methods Population-based cohort study of patients contacting three EDs in the North Denmark Region during 2014-2016, excluding injured patients. Main diagnoses, number of revisits within 72 h of the initial contact and mortality were outcomes. Data on age, sex, mortality, time of admission and ICD-10 diagnostic chapter were obtained from the Danish Civil Registration System and the regional patient administrative system. Descriptive statistics were applied and Kaplan Meier mortality estimates with 95% CI were calculated. Results Seventy-nine thousand three hundred forty-one short-term ED contacts were included, visits constituted 60%. Non-specific diagnoses (i.e. symptoms and signs and other factors) were the most frequent diagnoses among both visits and short stay visits groups (67% vs 49%). Revisits were more frequent for visits compared to short stay visits (5.8% vs 4.2%). Circulatory diseases displayed the highest 0-48-h mortality within the visits and infections in the short stay visits (11.8% (95%CI: 10.4-13.5) and (3.5% (95%CI: 2.6-4.7)). 30-day mortality were 1.3% (95%CI: 1.2-1.5) for visits and 1.8% (95%CI: 1.7-2.0) for short stay visits. The 30-day mortality of the ED revisits with an initial visit was 1.0% (0.8-1.3), vs 0.7% (0.7-0.8) for no revisits, while 30-day mortality nearly doubled for ED revisits with an initial short stay visit (2.5% (1.9-3.2)). Conclusions Most patients were within the visit group. Non-specific diagnoses constituted the majority of diagnoses given. Mortality was higher among patients with short stay visits but increased for both groups with ED revisits. This suggest that diagnostics are challenged by short time targets.